THE ROLE OF FAIRYTALES IN TEACHING ENGLISH AT A PRIMARY SCHOOL LEVEL - Baisov, Akhmad (Журнал иностранных языков и лингвистики, 2021)
The overall aim of the thesis is to show benefits of fairy tales for the development of young children not only within the “walls” of school classroom but in their lives as well. Hopefully, the usage of fairy tales in English lessons will help learners to appreciate the literature of target language and build up positive attitude towards literature in general. In this essay, the role of fairytales as a lingo-didactic material in English language classes will be thoroughly discussed. Keywords